Pre-Service English Teachers’ Perceptions of Teaching Strategies in English Learning for Adolescents - Muhammad Imam Lazuardi; Pasca Kalisa (Universitas Pahlawan Tuanku Tambusai, 2026)
Teaching adolescent learners in English as a Foreign Language (EFL) classroom requires instructional strategies that address not only language development but also students’ cognitive, social, and emotional characteristics. Previous studies have examined pre-service teachers’ beliefs, teaching practices, and practicum experiences in general EFL settings. However, limited research has specifically explored how pre-service English teachers perceive the suitability of various teaching strategies for adolescent learners and what factors influence those perceptions during teaching practicum. This issue is important because perceptions formed during practicum often shape future instructional decisions and professional teaching identities. Therefore, a deeper understanding of pre-service teachers’ views can provide valuable insights into teacher education and classroom practice. This study investigates pre-service English teachers’ perceptions of teaching strategies for adolescent students and the factors shaping those perceptions during practicum. Using a qualitative descriptive design, the study involved 40 pre-service English teachers from Universitas Negeri Semarang who participated in the LANTIP 6 practicum program. Data were collected through a 20-item Likert-scale questionnaire and follow-up semi-structured interviews with five selected participants. The findings indicate that participants generally favored strategies that promote active participation, provide clear scaffolding, and create a low-anxiety learning environment. Interview data further revealed that strategy selection was influenced by students’ confidence, proficiency differences, classroom management challenges, time constraints, mentor expectations, and available facilities. These findings suggest that pre-service teachers view teaching strategies as contextual and adaptive practices shaped by real classroom conditions rather than as fixed instructional techniques.